The current trends and challenges towards good community pharmacy practice and the way forward - Alein W. Bou-Saba; Kassem M. Kassak; Pascale R. Salameh (Elsevier, 2022)
Background: The practice of pharmacy continues to evolve. Comprehensive research to monitor and assess the development of the practice is needed. Good Pharmacy Practices (GPP) have been adopted by many countries to enhance the quality of services. Little information is available concerning how pharmacy practices are being implemented in developing countries. Lebanon being a developing country is a good example where community pharmacy practice doesn't follow clear guidelines and no evidence of good clinical practice. Objectives: This study aims to highlight GPP implementation, to identify obstacles impeding implementation, and to suggest how its application could be facilitated in Lebanon. Methods: The review included studies published in English during the last five years covering aspects of pharmacy practice in relation to GPP standards. The search excluded research related to hospital pharmacy practice and primary health care centers since they have their own quality standards. Results: The research identified 20 recent studies that covered aspects of community pharmacy practice in Lebanon in relation to GPP standards. Eight of the studies related to research and professional development,5 related to the provision of medicines,4 related to interaction and communication,1 related to trainees,1 related to pharmacotherapy monitoring, and 1 related to documentation systems. An additional 6 studies provided insight into factors that affect the pharmacy practice in general. It is apparent that the pharmacy practice would benefit if pharmacists were better supported with financial incentives and a readjustment of their working conditions as this would have a positive impact on their productivity, job satisfaction, and overall well-being. The review indicated that the standard of research and professional development was the most studied topic and it was recommended that pharmacists develop their research capabilities. It was observed that there is a tendency towards implementing Continuous Education for pharmacists and obstacles primarily included work and family commitments, lack of interest, lack of time, difficulties in commuting, and lack of competence in the use of technology. This standard is aligned with the FIP's developmental goal of continuing professional development strategies. The search also identified only one pilot study to assess GGP compliance among community pharmacies in Lebanon. This pilot study was limited and showed low adherence of community pharmacies in Lebanon to GPP standards.Barriers to implementation are lack of enforcing laws,inadequate dissemination of the standards among the community pharmacists, poor public perception, and the financial and soscioeconomically crisis facing Lebanon. Conclusion: Collaborated efforts are needed to implement GPP standards in Lebanon.It is recommended to undergo training and awareness sessions to community pharmacists thus enhancing their commitment and motivation. It is also recommended to establish key performance indicators to monitor the implementation. İndicators should include structure indicators for regulating the storage of medications, process indicators for regulating the dispensing, and outcome indicators for reporting patient safety incidents, measuring public satisfaction and the provision and use of medicines.These recommendations can be used by Health authorities and Pharmacy educational institutions in Lebanon and in all similar low-income countries.